Lectotypification of Panicum salzmannii, basionym of Isachne salzmannii (Poaceae, Micrairoideae) - Rodrigues, Rodrigo Sampaio; Dórea, Marcos Da Costa; Filgueiras, Tarciso De Sousa; de Oliveira, Reyjane Patrícia (Phytotaxa, 2016)
In Poaceae, many species names now accepted in distinct genera were originally described in Panicum Linnaeus (1753: 55), such as P. salzmannii Trinius ex Steudel (1854: 95), which is now recognized as a species of Isachne Brown (1810: 196) [i.e., P. salzmannii is the basionym of I. salzmannii (Trin. ex Steud.) Renvoize (1984a: 184)].